Purification and characterization of α-amylase from Paenibacillus sp. D9 and Escherichia coli recombinants. Issue 1 (2nd January 2020) - Naidu, Kayleen; Maseko, Sibusiso; Kruger, Gert; Lin, Johnson
Abstract: The aim of this study was to purify and characterize α-amylase of Paenibacillus species D9 and cloned α-amylase in Escherichia coli transformants. Optimal growth and production of D9 α-amylase were obtained after the 24-h incubation period, at pH 7, 30 °C and 200 rpm, using starch as the sole carbon source. Sodium nitrate stimulated α-amylase production by 3 folds while urea had an inhibitory effect comparing with yeast extract as the control. Characterization results of the crude and purified enzyme were similar. Purified D9 α-amylase possessed 97% residual activity after incubation at 30 °C for 120 min while 50% at 45 °C and 27% at 60 °C, respectively, under the same condition. The presence of Ca 2+ ions enhanced the activity, while EDTA and Fe 3+ had an inhibitory effect. Kinetic parameters were obtained having values of 37.3 mM, 19.8 U/mg and 4.84 s −1 for Km, V max and kcat, respectively. The α-amylase gene ( amyS ) of Paenibacillus sp. D9 was amplified using polymerase chain reaction (1482 bp), cloned into PSF-OXB20 vector and expressed in E. coli BL21 DE3 (pLysS) after transformation. The α-amylase purified from the transformant using a Hispur Cobalt column possessed 1.4 folds (450.8 U/mg) higher specific activity than the purified α-amylase from the wild type. Cloned α-amylase was more thermostable at 45 °C and at 60 °C, but less pH stable at pH 5 and 6. All other biochemical properties of the native and recombinant α-amylase show no significant differences. In conclusion, α-amylase of Paenibacillus sp. D9 was purified, cloned and characterized. The potential biotechnological application(s) of α-amylase may be explored.